2021
DOI: 10.1001/jamanetworkopen.2021.2274
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory, Clinical, and Survival Outcomes Associated With Peptide Receptor Radionuclide Therapy in Patients With Gastroenteropancreatic Neuroendocrine Tumors

Abstract: IMPORTANCE Peptide receptor radionuclide therapy (PRRT) is approved in the US for treatment of gastroenteropancreatic neuroendocrine tumors (NETs), but data on PRRT outcomes within US populations remain scarce. OBJECTIVE To analyze the first 2 years of PRRT implementation at a US-based NET referral center. DESIGN, SETTING, AND PARTICIPANTS This cohort study was conducted using medical records of patients with metastatic NET receiving PRRT from 2018 through 2020 in a NET program at a tertiary referral center. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 24 publications
(56 reference statements)
2
22
0
Order By: Relevance
“…1,2 However, DLTs occur in a limited number of patients with a particular predilection for bone marrow and kidney toxicity. [1][2][3][4][5][6][7][8][9][10][11][12] In this study, we have demonstrated that after treatment with 177 Lu-DOTATATE, female NET patients have a higher risk of developing DLTs of platelets and hemoglobin than male subjects. The DLTs of thrombocytopenia are defined as platelet counts less than 75 Â 10 9 /L (CTCAE grade ≥2).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, DLTs occur in a limited number of patients with a particular predilection for bone marrow and kidney toxicity. [1][2][3][4][5][6][7][8][9][10][11][12] In this study, we have demonstrated that after treatment with 177 Lu-DOTATATE, female NET patients have a higher risk of developing DLTs of platelets and hemoglobin than male subjects. The DLTs of thrombocytopenia are defined as platelet counts less than 75 Â 10 9 /L (CTCAE grade ≥2).…”
Section: Discussionmentioning
confidence: 99%
“…A case series on 5 patients with bone marrow infiltration of NETs and myelosuppression demonstrated that PRRT could be safe also in these patients when prophylactic peripheral blood stem cell collection was performed before PRRT ( 29 ). In another study, grade 1–2 hematological toxicities were observed in 60.3% of patients and grade 3–4 toxicities were observed in 25 patients (32.1%), without the development of myelodysplasia or the need for dialysis or liver failure ( 27 ).…”
Section: Resultsmentioning
confidence: 97%
“…Despite optimal treatment with SSAs, patients may still experience diarrhea and flushing, particularly in severe cases [18]. Thus, peptide receptor radionuclide therapy (PRRT) has been considered a second-line treatment option for carcinoid syndrome refractory to SSAs [18][19][20]. Furthermore, PRRT with 177Lu-DOTATATE was approved in 2018 by the FDA for treating gastroenteropancreatic NETs (GEP-NETs), administered intravenously.…”
Section: Peptide Receptor Radionuclide Therapymentioning
confidence: 99%
“…They target somatostatin receptors, which are highly expressed in well-differentiated NETs. Therefore, PRRT is indicated for patients with advanced inoperable well-differentiated GEP-NETs [18][19][20]. Although PRRT is well-tolerated, the most common adverse reactions reported are nausea and vomiting.…”
Section: Peptide Receptor Radionuclide Therapymentioning
confidence: 99%